Influência das condições bióticas e abióticas locais e da mudança no uso do solo sobre a dinâmica populacional de grupos bacterianos cultiváveis e sua relação com os ciclos biogeoquímicos - Cavalcante, Fernando Gouveia (2022)
Soil degradation is the result of the sum of geological, climatic, biological and human factors thatlead to the reduction of its physical, chemical and biological potential, putting biodiversity andhumanity at risk. Land use change is a threat to environmental conservation, as it causes soildegradation, affecting ecosystem functions and services. Biogeochemical cycling is closelyassociated with microorganisms, of which functional groups and actinobacteria stand out, butthese are susceptible to soil disturbances. The objective of this work was to investigate how localbiotic and abiotic conditions and land use change affect the population dynamics of bacterialfunctional groups and actinobacteria on regional scale and their relationship with carbon (C),nitrogen (N) and phosphorus (P) contents. This study included four locations with distinctenvironmental characteristics: Aiuaba; Sete Cidades; Ubajara 1 and Ubajara 2. Land use classeswere established based on the successional status of native vegetation and agricultural activity.Soil samples were analyzed for chemical parameters and the quantification of cultivable bacterialgroups was performed by the plate viable counting method. The population dynamics wasrepresented by the abundance of each bacterial group. The data was submitted to MANOVA andlinear regression analysis relating the abundances with soil C, N and P contents. Redundancy andprincipal component analyzes were used to identify which factors most influence bacterialpopulation dynamics on a local and regional scale, respectively. The results showed that on aregional scale, local conditions have a greater effect on the variance of bacterial groups than landuse changes, and soil pH was the main factor influencing bacterial abundances. Sete Cidades wasthe location most negatively affected by the studied factors. Greater interaction betweenmicrobial abundances and C, N and P contents was observed in Ubajara 1 and Ubajara 2, whichis related to the greater organic carbon availability in these locations. Soil nitrogen was theelement most affected by bacterial abundances. It is concluded that land use change has a greaterimpact on bacterial population dynamics in environments with greater abiotic severity.